Clinical data and basal gonadotropins in the diagnosis of central precocious puberty in girls - Durá-Travé, Teodoro (Endocr Connect, 2021)
OBJECTIVE: The objective of this study was to analyze whether some auxological characteristics or a single basal gonadotropin measurement will be sufficient to distinguish the prepubertal from pubertal status. METHODS: Auxologycal characteristics were recorded and serum LH and FSH were measured by immunochemiluminescence assays before and after GnRH stimulation test in a sample of 241 Caucasian girls with breast budding between 6- and 8-years old. Peak LH levels higher than 5 IU/L were considered a pubertal response. Area under the curve, cut-off points, sensitivity, and specificity for auxologycal variables and basal gonadotropins levels were determined by receiver operating curves. RESULTS: There were no significant differences in age at onset, weight, height, BMI and height velocity between both groups. Bone age was significantly higher in pubertal girls (P < 0.05), although with limited discriminatory capacity. The sensitivity and specificity for the basal LH levels were 89 and 82%, respectively, for a cut off point of 0.1 IU/L. All girls in the pubertal group had a basal LH higher than 1.0 IU/L (positive predictive value of 100%). There was a wide overlap of basal FSH and LH/FSH ratio between prepubertal and pubertal girls. CONCLUSIONS: Auxologycal characteristics should not be used only in the differential diagnosis between prepubertal from pubertal status in 6- to 8-year-old girls. We found a high specificity of a single basal LH sample and it would be useful for establishing the diagnosis of puberty in this age group, reducing the need for GnRH stimulation testing.